Efecto de la cal y la urea en el manejo del moko de las musaceas - Nuñez, G.=700 1 Guevara, G.; Monterroso, D.
(Es)
ilus., 5 ref.
Keywords: PSEUDOMONAS SOLANACEARUM; TRATAMIENTO DEL SUELO; MOKO DE LAS MUSACEAS; SANEAMIENTO DEL SUELO